2013
DOI: 10.3945/ajcn.113.059600
|View full text |Cite
|
Sign up to set email alerts
|

Telephone-based support prolongs breastfeeding duration in obese women: a randomized trial

Abstract: Telephone-based advisory support was very effective in prolonging breastfeeding in obese mothers who often terminate the breastfeeding of their infants prematurely. A longer duration of breastfeeding may decrease risk of noncommunicable diseases in these infants. This trial was registered at clinicaltrials.gov as NCT01235663.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
93
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(97 citation statements)
references
References 29 publications
3
93
1
Order By: Relevance
“…Chapman et al tested a peer counselor intervention tailored to the perceived needs of overweight and obese women among 206 women in Connecticut and found higher rates of any and >50% breastfeeding at 2 weeks postpartum, but no other differences in breastfeeding rates 81 . Carlsen et al tested an IBCLC phone support intervention among 226 obese women in Denmark and increased both any and exclusive breastfeeding duration 82 . Carlsen's findings suggest that targeted support may improve outcomes among women at metabolic risk, but it remains to be determined what strategy may be most effective within the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Chapman et al tested a peer counselor intervention tailored to the perceived needs of overweight and obese women among 206 women in Connecticut and found higher rates of any and >50% breastfeeding at 2 weeks postpartum, but no other differences in breastfeeding rates 81 . Carlsen et al tested an IBCLC phone support intervention among 226 obese women in Denmark and increased both any and exclusive breastfeeding duration 82 . Carlsen's findings suggest that targeted support may improve outcomes among women at metabolic risk, but it remains to be determined what strategy may be most effective within the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, intervention studies attempting to improve breastfeeding rates have been limited in effectiveness (Chapman et al, ; Rasmussen, Dieterich, Zelek, Altabet, & Kjolhede, ). One intervention among women with a BMI ≥30 kg/m 2 significantly improved rates of exclusive and any breastfeeding across the postpartum period (Carlsen et al, ); however, underlying mechanisms of action were not identified as psychosocial factors were unaccounted for throughout. A proposed Cochrane review evaluating evidence available for breastfeeding support and interventions in this cohort likewise ignores the role of social cognitive and psychological associations (Soltani & Fair, ).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, control mothers could elect to enroll in the prenatal clinic's free lactation peer-support program. Carlsen et al tested an International Board-Certified Lactation Consultants (IBCLC) phone support intervention for obese women in Denmark, 48 and found that the intervention significantly increased duration of exclusive breastfeeding (median 120 days vs. 41 days). Bonuck et al tested an integrated pre- and post-natal IBCLC intervention among 990 women, two-thirds of whom were overweight or obese.…”
Section: Implications For Clinical Carementioning
confidence: 99%